Sarcosine influences apoptosis and growth of prostate cells via cell‐type specific regulation of distinct sets of genes. Issue 2 (6th November 2017) - Rodrigo, Miguel A. Merlos; Strmiska, Vladislav; Horackova, Eva; Buchtelova, Hana; Michalek, Petr; Stiborova, Marie; Eckschlager, Tomas; Adam, Vojtech; Heger, Zbynek
Abstract : Background: Sarcosine is a widely discussed oncometabolite of prostate cells. Although several reports described connections between sarcosine and various phenotypic changes of prostate cancer (PCa) cells, there is still a lack of insights on the complex phenomena of its effects on gene expression patterns, particularly in non‐malignant and non‐metastatic cells. Methods: To shed more light on this phenomenon, we performed parallel microarray profiling of RNA isolated from non‐malignant (PNT1A), malignant (22Rv1), and metastatic (PC‐3) prostate cell lines treated with sarcosine. Microarray results were experimentally verified using semi‐quantitative‐RT‐PCR, clonogenic assay, through testing of the susceptibility of cells pre‐incubated with sarcosine to anticancer agents with different modes of actions (inhibitors of topoisomerase II, DNA cross‐linking agent, antimicrotubule agent and inhibitor of histone deacetylases) and by evaluation of activation of executioner caspases 3/7. Results: We identified that irrespective of the cell type, sarcosine stimulates up‐regulation of distinct sets of genes involved in cell cycle and mitosis, while down‐regulates expression of genes driving apoptosis. Moreover, it was found that in all cell types, sarcosine had pronounced stimulatory effects on clonogenicity. Except of an inhibitor of histone deacetylase valproic acid, efficiency of all agents was significantly ( P < 0.05) decreased in sarcosine pre‐incubated cells. Conclusions: Our comparative study brings evidence that sarcosine affects not only metastatic PCa cells, but also their malignant and non‐malignant counterparts and induces very similar changes in cells behavior, but via distinct cell‐type specific targets.